VD_FINDINFO AI 231/08 - 155/2011 vom 23. März 2011 - VD Tribunal cantonal (2011)
FORCE PROBANTE, ASSURANCE-VIEILLESSE, SURVIVANTS ET INVALIDITÉ, DEGRÉ DE L'INVALIDITÉ | 28 LAI, 4 al. 1 LAI, 16 LPGA, 7 LPGA, 8 al. 1 LPGA